Measuring performance of invasive plant eradication efforts in New Zealand - Holloran, P. (New Zealand Plant Protection, 2006)
New Zealands Biosecurity Act 1993 which has enabled local governments to pursue eradication of 69 different invasive plant taxa is strongly influenced by new public management doctrine and its emphasis on specific management objectives annual plans and performance measures Data to support meaningful eradication performance measures are still rare despite such requirements It can take several decades to achieve eradication since seed banks and other factors often complicate invasive plant eradication efforts Since eradication of all sites is often preceded by the gradual elimination of some infestations evaluating trends in site status (whether aboveground plants are present or absent) and site population size (based on complete censuses) may help biosecurity staff to evaluate progress improve eradication efforts and communicate their successes These performance measures are illustrated using a 7year dataset from Raoul Island